Assessment of the mechanical behaviour of reinforcement bars with localised pitting corrosion by Digital Image Correlation. (15th September 2020) - Chen, E.; Berrocal, Carlos G.; Fernandez, Ignasi; Löfgren, Ingemar; Lundgren, Karin
Highlights: Strength (based on minimum residual area of corroded bars) was almost constant. Steel outside the pit did not yield when critical corrosion level was exceeded. Analytical lower-bound model was given for ultimate strain. Semi-analytical model was developed to calculate ultimate strain at any gauge length. Ultimate strain depends on corrosion level, pit morphology and gauge length. Abstract: Corrosion of reinforcement in concrete impairs the mechanical behaviour of rebars by decreasing their strength and deformation capacity. In this study, uniaxial tensile tests were carried out on 61 rebars taken from 22 pre- and un- cracked reinforced concrete beams subjected to drying and wetting cycles in chloride solution for over three years. A 3D-scanning technique was used to characterise the maximum local corrosion level, μ max, and different pit shape parameters. Digital Image Correlation (DIC) was used to capture the displacement field of the test bars; the engineering strain was measured through the virtual extensometers created in the DIC post-processing software. The proof and ultimate forces showed linear decreasing trends of μ max, while the proof and ultimate strengths (based on the minimum residual cross-sectional area) were not obviously affected by corrosion. The ultimate strain of corroded bars depended on the gauge length due to strain localisation in the pit. Thus, it was emphasised that the ultimate strain may be overestimated if measured based on a short gauge across the pit. It was also observed that when μ max exceeded a critical local corrosion level ( μ crit depending on the ratio between the yield and ultimate strengths of the steel), the region outside the pit did not develop yielding. A lower bound of ultimate strain was further derived as a function of the mechanical parameters of uncorroded steel and maximum local corrosion level. This provided a good comparison with the experimental results. Ultimately, a hypothesis for time-dependent assessment of strain capacity is proposed, considering the evolution of corrosion morphology over time.